Green Innovation for Enhanced Competitiveness and Financial Performance: A Study of Ultra-Micro and Micro Craft Businesses in Indonesia - Dyah Arini Rudiningtyas; Sudarmiatin; Ludi Wisnu Wardana (CV. AFDIFAL MAJU BERKAH, 2024)
This study investigates the relationship between green innovation, competitiveness, and financial performance in ultra-micro and micro craft businesses in West Java, Indonesia. Using a quantitative exploratory approach, data were collected via structured surveys from 403 craft business units, involving both business owners and managers. The survey employed a Likert scale to assess green innovation, competitiveness, and financial performance. Partial least squares structural equation modeling (PLS-SEM) was used to analyze the data. The findings reveal that business competitiveness mediates the impact of green innovation on financial performance. However, green innovation has no significant effect on financial performance. Additionally, business size significantly moderates the relationship between competitiveness and financial performance, with larger businesses better able to leverage competitive advantages for financial success. The study recommends that craft businesses invest in sustainable practices and scale up operations to enhance their competitiveness and achieve long-term financial growth. These insights are valuable for policymakers and business owners alike.